Double dielectric barrier (DBD) plasma-assisted deposition of chemical stabilized nanoparticles on polyamide 6,6 and polyester fabrics - Ribeiro, Ana (2017)
Abstract. The development of new multifunctional textiles containing nanoparticles (NPs) has a special interest in several applications for pharmaceutical and medical products. Cu, Zn and Ag are the most promising antimicrobial NPs, exhibiting strong antibacterial activities. However, most of antimicrobial textiles coated with NPs are not able to perform a controlled release of NPs because of the high degree of aggregation. The aim of this study is to assess the effect of NPs stabilizers such as citrate, alginate and polyvinyl alcohol (PVA) in Cu, Zn and Ag NPs dispersions. The obtained dispersions were used to develop a new class of antibacterial NPs coatings onto polyamide 6,6 (PA66) and polyester fabrics (PES) by Double Dielectric Barrier (DBD) plasma discharge. Dynamic light scattering (DLS) was used to evaluate the best dispersing agent in terms of size, polydispersity index and zeta potential. Coating efficiency was evaluated by SEM, XPS and FTIR. The washing fastness of the coatings developed was also tested. The results show that the best dispersions were obtained using 2.5% of citrate for ZnO, 5% Alginate for Cu and 2.5% alginate for Ag NPs. SEM, XPS and FTIR analysis shows that DBD is an efficient deposition technique only for Ag and Cu NPs and that better perform in PA66 than PES fabric. The DBD deposition in air display similar results in term of NPS deposition of usually more efficient plasma jets using carrier gas such as N2 and Ar.